Development of Attendance Information System For Teacher Attendance at Pertiwi Elementary School Bandung - Dewi, Irma Amelia; Miftahuddin, Yusup; Triseptiyadi, Fahmi; Vito, Nicola; Naufal, Muhammad Thoriq; Fahreza, Algi (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2024)
The advancement of technology particularly in telecommunications, has led to the creation of various software applications that are beneficial to human life. One such application is modern attendance management systems. The objective of this research is to construct and implement a QR-code-based attendance information system for teachers and staff at SD Pertiwi Kota Bandung. The research methodology comprises socialization, counseling, implementation, and monitoring and evaluation. The responses indicate that the application has met or exceeded user expectations in terms of functionality and accessibility. Of the respondents, 30.74% gave "Normal" responses, 41.85% gave "Baik" responses, and 27.41% gave "Sangat Baik" responses. Additionally, the responses from program partners, SD Pertiwi, Bandung City, indicate positive evaluation and feedback.. The results of this development are intended to improve the accuracy of the attendance process, facilitate teachers and staff in reporting attendance, and minimize fraud and human error.